Poor Unstable Midgut Microbiome of Hard Ticks Contrasts With Abundant and Stable Monospecific Microbiome in Ovaries - Guizzo, Melina Garcia; Neupane, Saraswoti; Kucera, Matej; Perner, Jan; Frantová, Helena; da Silva Vaz, Itabajara; Oliveira, Pedro L. de; Kopacek, Petr; Zurek, Ludek (Frontiers in Cellular and Infection Microbiology, 2020)
Culture-independent metagenomic methodologies have enabled detection and identification of microorganisms in various biological systems and often revealed complex and unknown microbiomes. In many organisms, the microbiome outnumbers the host cells and greatly affects the host biology and fitness. Ticks are hematophagous ectoparasites with a wide host range. They vector a number of human and animal pathogens and also directly cause major economic losses in livestock. Although several reports on a tick midgut microbiota show a diverse bacterial community, in most cases the size of the bacterial population has not been determined. In this study, the microbiome was quantified in the midgut and ovaries of the ticks Ixodes ricinus and Rhipicephalus microplus before, during, and after blood feeding. Although the size of bacterial community in the midgut fluctuated with blood feeding, it was overall extremely low in comparison to that of other hematophagous arthropods. In addition, the tick ovarian microbiome of both tick species exceeded the midgut 16S rDNA copy numbers by several orders of magnitude. This indicates that the ratio of a tick midgut/ovary microbiome represents an exception to the general biology of other metazoans. In addition to the very low abundance, the tick midgut diversity in I. ricinus was variable and that is in contrast to that found in the tick ovary. The ovary of I. ricinus had a very low bacterial diversity and a very high and stable bacterial abundance with the dominant endosymbiont, Midichloria sp. The elucidation of this aspect of tick biology highlights a unique tissue-specific microbial-invertebrate host interaction.